Deficiência visual: Noções introdutórias - Cunha, Junior (2020)
The current conception of the term “disability” is a milestone in the history of inclusion of people with disabilities. Anchored on the principles that underlie the Universal Declaration of Human Rights (1948), the current definition of the term seeks to recognize and, thus, overcome the oppressions faced by people with disabilities over years of exclusion and prejudices that have been stigmatized in the lower strata. of the epidermis of societies built throughout history. This chapter was designed to meet the above, since our objective is to offer introductory notions about visual impairment and, thus, to deconstruct the impressions loaded with preconceptions about the theme. To that end, we highlight the person with visual impairment and not their impairment.